The Legal Politics of Formality and Substance of the Medina Constitution - Jamrud Zaman (TSAQAFAH, 2024)
The Medina Charter is considered the first constitution in the world because it has almost the same content as the modern constitution. So the study of the discussion of the history of the establishment of the Medina Charter, the politics of law, and the content of the material content is very necessary to be examined to be a material renewal of the modern constitution today. This research aims to be a comparative material with modern constitutions and as a material for constitutional reform in any country. This research is normative research with historical and comparative approaches. The data source of this research uses a literature study by tracing books and journals. While the data analysis method uses content analysis. The Medina Charter was formed by the Prophet Muhammad SAW. when he came to Medina to create peace and form a force to protect the city of Medina from outside attacks. The Medina Charter in the concept of Philippe Nonet and Philip Selznick's legal criteria includes responsive law because it contains characteristics, namely democratic making, equality in law, no partiality, made for public needs, and shared morality realized for the common good. The Medina Charter is said to be the first modern constitution in the world because its content is in line with modern constitutions, namely the protection of human rights, duties and obligations of citizens, politics of peace and unity, material provisions of the law, and state institutions.